2003
DOI: 10.1046/j.1365-2249.2003.02076.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced chemokine response in experimental acuteEscherichia colipyelonephritis in IL-1β-deficient mice

Abstract: SUMMARYThe aim of the present study was to investigate the effects of IL-1 b and Escherichia coli on the expression and secretion of MIP-2, the mouse equivalent to human IL-8, MCP-1 and RANTES in the kidneys of mice with acute pyelonephritis. Female Bki NMRI, as well as IL-1 b deficient mice and their wild-type littermates, were transurethrally infected with either E. coli CFT 073 or injected with NaCl 0·9% (w/v) and thereafter obstructed for 6 h. The Bki NMRI mice were killed at 0, 24, 48 h and 6 days and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 42 publications
1
37
0
Order By: Relevance
“…The CCR2 ligand, MCP-1 (CCL-2), has been shown to be secreted in cystitis and pyelonephritis (2,12), suggesting a functional role in these infections. However, bacterial clearance from the bladders of infected CCR2-deficient mice was unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…The CCR2 ligand, MCP-1 (CCL-2), has been shown to be secreted in cystitis and pyelonephritis (2,12), suggesting a functional role in these infections. However, bacterial clearance from the bladders of infected CCR2-deficient mice was unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there was a significant negative corre- lation between PC level and the degree of tissue pathology (r 2 ϭ Ϫ0.73, P Ͻ 0.001). During polymicrobial sepsis, chemokines including CXCL1 and CXCL2 show a progressive induction that is associated with ARF (10,11). Therefore, we examined the expression of both CXCL1 and CXCL2 in the kidneys of both sham and CLP rats.…”
Section: Endogenous Pc and Renal Pathologymentioning
confidence: 99%
“…Knowledge of the effects of cytokine regulation on the process of UTI has recently improved (1,2) and insights into the pathogenesis, genesis, and outcome of VUR and renal scarring also have been made (3). Many in vitro studies have shown that the expression of individual cytokines or cytokine receptors is influenced by polymorphic genotypes within regulatory regions, and that these polymorphic genotypes may play pivotal roles in the pathogenesis and progression of chronic renal diseases (4).…”
mentioning
confidence: 99%